Made in Vlissingen. - van der Wijst, Machteld; Bommeljé, Hans; de Nennie, Ramon; Swiers, Robbert Jan (Middelburg : Stichting decreet-concreet, 2013)
Ruedisueli, Ria ; Haas, Jan ; Hofman, Wim ; Roovers, Kees ; de Jonge, Ko ; Quite, Bert ; Meijer, Rob ; Quite, Rob ; Steutel, Peter ; Riekwell, Leon ; Dalstra, Koos ; Overvliet, Hans ; Kesteloo, Carla ; Viergever, Frank ; Grootjans, Loek ; Bommeljé, Hans ; Spit, Sebastiaan ; Golembiewski, Jeanny ; Rouwendal, Petra ; Jasperse, Monique ; Voit, Barbara ; de Muynck, Mischa ; van den Bosch, Rem ; Bianchet, Nicole ; Bonneur, Eva ; Paalvast, Michiel ; Vrielink, Tjeerd ; Gerestein, Femke
boek